EDUCATIONAL REFORMS UNDERTAKEN DURING THE TERM OF THE PRESIDENT OF THE REPUBLIC OF UZBEKISTAN SHAVKAT MIRZIYOYEV (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article analyzes the reforms in the education system being implemented at the initiative of the President of the Republic of Uzbekistan Shavkat Mirziyoyev. The changes being made in the processes from preschool to higher education, innovative approaches and directions for the implementation of international experiences are considered. The impact of these reforms on national development is also studied.